Sociedade em crise: uma leitura de Sueños digitales (2000) e El delirio de turing (2003) - Eulálio Marques Borges (2019)
Considering that Sueños Digitales (2000) and El delirio de Turing (2003) by the bolivian writer Edmundo Paz Soldán have been so little studied by literary critics, both novels are analyzed in this thesis, aiming at emphasizing the idea of Río Fugitivo, where the stories take place, as a society in crisis and with characters in crisis. In order to do so, we start with the analysis of the similarities and differences between the two plots and the contemporary science fiction. Such similarities and differences work as a way of highlighting the imaginary city as a chaotic, stratified place, not rarely in armed conflict and populated by subjects who establish complex relationships with the technologies to which they have access, such as internet and photography. Many of the individuals, who are seen here as the outcome of such a problematic place, end up developing diverse paranoid personalities, aggressive or not, which are characterized by persecutory delusions, megalomania and even visual and auditory hallucinations, among other characteristics. The concept of a topos in crisis with characters in crisis is strengthened when we observe some of the expressions of trivialized and embellished violence that pervade the narratives, going beyond the issue of the power desired by some of the characters created by Paz Soldán. All of these topics, apparently with no connections between them, are intertwined along stories that flirt with the science fiction, particularly with the cyberpunk and dystopia subgenres, more precisely with the idea of ficción paranoica (paranoid fiction). Thus, it is possible to find echoes of contemporaneity, which leads to thoughts and discussions about the current world, showing us how literature also can be a way of reading into and interpreting it and, maybe, even facing what surrounds us.